SIRT1 Functions as an Important Regulator of Estrogen-Mediated Cardiomyocyte Protection in Angiotensin II-Induced Heart Hypertrophy. (29th December 2014) - Shen, Tao; Ding, Ling; Ruan, Yang; Qin, Weiwei; Lin, Yajun; Xi, Chao; Lu, Yonggang; Dou, Lin; Zhu, Yuping; Cao, Yuan; Man, Yong; Bian, Yunfei; et al.
Abstract : Background . Sirtuin 1 (SIRT1) is a member of the sirtuin family, which could activate cell survival machinery and has been shown to be protective in regulation of heart function. Here, we determined the mechanism by which SIRT1 regulates Angiotensin II- (AngII-) induced cardiac hypertrophy and injury in vivo and in vitro. Methods . We analyzed SIRT1 expression in the hearts of control and AngII-induced mouse hypertrophy. Female C57BL/6 mice were ovariectomized and pretreated with 17 β -estradiol to measure SIRT1 expression. Protein synthesis, cardiomyocyte surface area analysis, qRT-PCR, TUNEL staining, and Western blot were performed on AngII-induced mouse heart hypertrophy samples and cultured neonatal rat ventricular myocytes (NRVMs) to investigate the function of SIRT1. Results . SIRT1 expression was slightly upregulated in AngII-induced mouse heart hypertrophy in vivo and in vitro, accompanied by elevated cardiomyocyte apoptosis. SIRT1 overexpression relieves AngII-induced cardiomyocyte hypertrophy and apoptosis. 17 β -Estradiol was able to protect cardiomyocytes from AngII-induced injury with a profound upregulation of SIRT1 and activation of AMPK. Moreover, estrogen receptor inhibitor ICI 182, 780 and SIRT1 inhibitor niacinamide could block SIRT1's protective effect. Conclusions . These results indicate that SIRT1 functions as an important regulator of estrogen-mediated cardiomyocyte protection during AngII-induced heart hypertrophy and injury.